Exploring Student Silence in EFL Speaking Classrooms: Teachers’ Perceptions and Classroom Strategies - Annisa Siti Aulia Muzdalifah; Willy Prasetya (Universitas Islam Negeri Palopo, 2026)
Student silence is often perceived as a barrier to participation in English as a Foreign Language (EFL) speaking classes, where verbal interaction is commonly viewed as an indicator of engagement and learning. However, silence may also reflect linguistic difficulties, emotional factors, and classroom dynamics rather than simple disengagement. This study explores the teacher’s perception of student silence, the factors contributing to it, and the strategies used to support the students during speaking activities. A qualitative descriptive design was employed, involving a semi-structured interview with one experienced English teacher at a public junior high school in Yogyakarta, Indonesia. The interview data were analyzed thematically to identify patterns related to silent behavior in classroom interaction. The findings indicate that silence is mainly associated with limited language proficiency, low confidence, fear of negative evaluation, and unfamiliarity with English, particularly among lower-grade students. Peer reactions and classroom expectations also influence the students’ willingness to speak. To address these challenges, the teacher implemented strategies such as structured preparation, prompting techniques, first-language support, and creating an emotionally safe classroom environment. This study highlights teachers’ perspectives on silence in Indonesian junior high school EFL classrooms and suggests that silence can be understood as part of the language learning process rather than merely a learning obstacle.